Auditoría de gestión y su relación en el cumplimiento del presupuesto del gobierno autónomo descentralizado del catón El Empalme año 2011 - Espinoza Vélez, Monserrate Yasmel (2013)
Decentralized Autonomous Government of Canton The Empalme, is a public institution with legal personality, with the state budget and indefinite duration. The objective of this research project is to examine the fiscal budget of the Autonomous Decentralized Canton Empalme to assess the level of compliance of the items budgeted in the period 2011, this process will determine the actual situation of economic investment allocated to the application of its planned activities to alleviate the basic elementary needs of its population. The actions will determine if resources are invested correctly, so it is necessary to perform an audit, in order to describe the budgeted financial statements are true of the same and thus resolve to meet your needs, this will conducted the audit based on the application of research techniques such as the interview realized to the Mayor and to the Chief financial officer, direct observation was applied to establish factors such as knowledge and fulfillment of obligations, planning, coordination, communication, environment and activities control, establishment of roles and responsibilities among others, to determine the quality of administrative management is decentralized autonomous Government of Canton Empalme. Gathering ideas relevant aspects of internal control, and was identified as the main problem is "the failure of the budget." Consequently the objective was to investigate the theoretical basis with which to describe the essential concepts in order to improve management performs Decentralized Autonomous Government of Canton The Empalme, so as to allow organizing and implementing activities to improve the financial department that integrates these are objectively established roles, responsibilities, policies and procedures to follow and also the rules governing the activities within the Municipal Government of The Empalme allowing staff to have a clear understanding of their status within it.